Data Security Challenges and Solutions in Cloud Computing: Critical Review - Al-Otaibi, Shuruq Zayed (Communications in Mathematics and Applications, 2022)
This paper was prepare, based on the sensitivity of data security topics, and based on the controversy surrounding cloud-computing security. Therefore, this paper aimed to contribute by providing some tips and directions related to cloud security through critical review for a number of recent studies. Then, extracting the most important latest problems and solutions that related to data security in cloud computing; and presenting them all in one study to become a comprehensive reference. The study found that the most important problems are data leakage, data remoteness, privacy and data segregation. As for the most important solutions that this paper reached to meet these challenges, were using practical strategies like models and standards, and using different emerging and programming technologies such as encryption, digital signatures, hashing, and blockchain, smart contracts, IoTs sensors and devices, edge computing, and fog computing. The study recommended researchers to conduct more theoretical and practical research on the subject, and recommended the cloud services providers to adopt several practical strategies and emerging technologies for higher protection.